544. Clonal Spread of Two Sequence Types of Carbapenem-Resistant Acinetobacter baumannii Blood Isolates at a Tertiary Care Hospital in South Korea Over 2.5 Years - Eun Kim, Seong (Open Forum Infect Dis, 2019)
BACKGROUND: The dissemination of carbapenem-resistant Acinetobacter baumannii (CRAB) became an urgent public health concern. A specific sequence type (ST) of A. bauamannii has been reported to be associated with severity of disease or mortality. This study aimed to determine the genetic relatedness of CRAB blood isolates cultured from patients at a tertiary care hospital and to investigate clinical characteristics and outcome of CRAB bacteremia. METHODS: CRAB blood isolates were collected between June 2016 and December 2018, and their clinical data were obtained. Multi-locus sequence test (MLST) was performed using the Oxford scheme, and the STs were assigned using the MLST database. RESULTS: Of the 126 CRAB blood isolates, 123 isolates which could be typed by MLST all belonged to clonal complex (CC) 92. During the entire period, ST369 (42.3%) was the most dominant, followed by ST191 (32.5%), ST784 (13.8%) and ST451 (4.1%). ST369 was firstly introduced in August 2017. ST191 (61.4%) was the most abundant during June 2016 to July 2017, whereas ST369 (65.8%) replaced ST191 (16.5%) since August 2017. The time interval between intensive care unit admission and bacteremia was shorter in ST369 than ST191 in multivariate analysis (day, median (Q1, Q3), ST369 6 (3, 9.8), ST191 9 (6, 17), Odd Ratio 0.87 (95% CI 0.76–0.99) P = 0.048 logistic regression). According to the ST, the 7-day and 30-day mortality rates were as follows; 46% and 65% in ST191, 50% and 62% in ST369, and 10.7% and 46.4% in the other STs. Patients infected by ST191 or 369 had significant higher 7-day mortality rates (ST191/369, 48.3% vs. the other STs 10.7%, P = 0.001 by log-rank test) and 30-day mortality rates (ST191/369, 63.2% vs. the other STs, 46.4%, P = 0.045 by log-rank test). CONCLUSION: This study demonstrates the clonal spread of two STs at a tertiary care hospital in South Korea over 2.5 years. After the introduction of ST369, it replaced ST 191 and widely disseminated within a hospital. Two predominant STs were associated with poor outcome. Continuous surveillance are necessary to monitor the dissemination of these strains. [Image: see text] DISCLOSURES: All authors: No reported disclosures.